Composition and Longitudinal Distribution of Fish Assemblages in the Estuary and Tributary Systems in RSU San Agustin, Romblon, Philippines - Mazo-Gonzalez, Xyrra Jeremiah C.; Mercano, Albert P.; Gonzalez, Jeric B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
This study examines the fish species composition and distribution across the estuary and its tributaries at RSU-San Agustin Campus, Romblon, Philippines. Fish communities in estuaries are structured by a variety of biotic and abiotic factors, including salinity gradients, water depth, substrate type, and food availability. Romblon, an archipelagic province in the central Philippines, is home to numerous estuarine and coastal ecosystems that play a vital role in sustaining local fisheries and biodiversity. A total of 39 fish species from 23 families were recorded across six sampling sites, with the Gobiidae family exhibiting the highest species representation. Species richness and diversity varied across the river sections, with the highest diversity observed at the river mouth, reflecting its role as a crucial transition zone between freshwater and marine ecosystems. The middle and upper reaches exhibited lower species richness, likely due to habitat specialization, environmental constraints, and anthropogenic influences. Shannon Diversity Index values indicated moderate biodiversity, while dominance indices revealed the prevalence of specific species in certain sites. The presence of commercially significant species such as Chanos chanos (milkfish) and Oreochromis niloticus (Nile tilapia) highlights the river system’s role in sustaining local fisheries. The River Mouth exhibits the highest species richness (26 species) and diversity (H' = 2.19), likely due to its estuarine nature, which supports a wide range of species by providing abundant food and habitat diversity. The low evenness index (J' = 0.22) suggests that a few species dominate the area. In contrast, lower and middle reach of River 1 Middle Reach, have the lowest species richness (6 and 5 species) and diversity (H' = 1.13 and 0.77), indicating that environmental conditions such as habitat limitations, reduced resource availability, or possible human disturbances may be affecting fish populations in the river. This study suggests that the estuary and its tributaries support a dynamic and ecologically valuable fish community, necessitating conservation efforts to protect critical habitats and ensure sustainable fisheries management. This study provides essential baseline data for future ecological monitoring and biodiversity conservation initiatives in estuarine environments.